PENGARUH PERBEDAAN WAKTU EKUILIBRASI TERHADAP KUALITAS SEMEN BEKU BABI LANDRACE DALAM PENGENCER DURASPERM MODIFIKASI DENGAN AIR BUAH LONTAR (Effect of different equilibration time on the quality of landrace boar frozen semen on modification diluent.... - Maria G. Mega; Wilmientje M. Nalley; Aloysius Marawali; Henederiana L. L. Belli (Universitas Nusa Cendana, 2022)
An experiment was carried out to recognize the effect of long equilibration time on the quality of spermatozoa and to obtain optimal equilibration time in the process cryopreservation of landrace pig semen. Semen was obtained from a landrace boar aged 2-3 years using glove hand method. The semen was than evaluated macroscopically and microscopically, good quality semen was diluted in a basic diluent, than kept for two hours at a temperature of 27-28oC. The semen were then centrifuged at 2000 rpm for 15 minutes, the supernatant was discarced and the pellets was re-diluted into basic diluent with a ratio of 1:1. Then, semen was diluted in treatment diluent with modified durasperm + 6% lactose + 4% glycerol with a concentration of 500 x 106/0.5 mL. Furthermore, the semen was packaged in 0.5 ml straws, then equilibrated at a temperature of 3-5oC appropriate to treatment, with 1 hour equilibration (T1), 2 hours equilibration (T2) and 3 hours equilibration (T3). After equilibration, the straws was frozen horizontally 5 cm above the liquid N2 vapor for 10 minutes at a temperature of ± -110oC and then stored in a liquid N2 container (-196oC). To test frozen semen, it was done by stored frozen semen at 37oC for 30 seconds. The results showed that the highest quality of spermatozoa (P <0.05) was found in T2 and T3 when compared to T1 (P> 0.05), with the motility value was T2: 28.13 ± 2.39%; T3: 25.00 ± 4.08%; and T1 18,15±3,23%. It can be concluded that 2 hours and 3 hours equilibration time was able to maintain the quality of frozen semen landrace boars and the statistically was not significant.